Penguatan Kemahiran Muhādatsah Mahasiswa Melalui Manajemen Kegiatan Berbasis Komunitas Bahasa Arab - Setiadi, Fadlan Masykura; Khairunnisa, Khairunnisa (Welfare : Jurnal Pengabdian Masyarakat, 2025)
The ability to speak Arabic among students of IAIN Langsa's Arabic Language Education Department (PBA) is not only important in an academic context, but also has potential as a means of social integration. Unfortunately, the use of Arabic outside the classroom is still limited and does not support the creation of a climate of togetherness across generations. This service program aims to strengthen the use of Arabic through a community-based participatory-collaborative approach, with muhādatsah training activities, lughawiyah discussion forums, Arabic outbound, and Arabic Language Day. The methods used include needs observation, intensive training, social language practice, and formative and summative evaluation. The results of the activity showed an increase in the courage to speak Arabic (muhādatsah), the frequency of social interaction between students, and the formation of new collaborative spaces. This activity not only contributes to strengthening linguistic competence, but also in forming an inclusive and sustainable academic social network.